Associations of sensory sensitivity, pain catastrophizing, and alexithymia with dental anxiety - Ogawa, Mika (WILEY, 2025)
We aimed to reveal interrelationships between alexithymia, catastrophic thinking, sensory processing patterns, and dental anxiety among 460 participants who were registrants of a Japanese research company. Measures used were the Modified Dental Anxiety Scale, the Adult Sensory Profile, the Pain Catastrophizing Scale, and the 20-item Toronto Alexithymia Scale. The interrelationships among the constructs were analyzed using structural equation modeling, adjusting for age, gender, and negative dental treatment experience. Data from 428 participants were used in the analyses. Sensory sensitivity and pain catastrophizing were independently associated with anticipatory and treatment-related dental anxiety, while difficulty identifying feelings was not. In the mediation model, sensory sensitivity and pain catastrophizing served as full mediators between difficulty identifying feelings and the dimensions of dental anxiety (indirect effects were between 0.13 and 0.15). The strength of the associations was 0.55 from difficulty identifying feelings to both pain catastrophizing and sensory sensitivity, and between 0.24 and 0.26 to anticipatory and treatment-related dental anxiety. The association between trait-like phenomena, such as alexithymia, and dental anxiety may be mediated by neurophysiological and cognitive factors such as sensory sensitivity and pain catastrophizing. These findings could be crucial for new and innovative interventions for managing dental anxiety.